12=-b-3b

Simple and best practice solution for 12=-b-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=-b-3b equation:


Simplifying
12 = -1b + -3b

Combine like terms: -1b + -3b = -4b
12 = -4b

Solving
12 = -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
12 + 4b = -4b + 4b

Combine like terms: -4b + 4b = 0
12 + 4b = 0

Add '-12' to each side of the equation.
12 + -12 + 4b = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 4b = 0 + -12
4b = 0 + -12

Combine like terms: 0 + -12 = -12
4b = -12

Divide each side by '4'.
b = -3

Simplifying
b = -3

See similar equations:

| 5d-7=2-4d | | 3(3-10x)=25(x+2) | | 2x^6+9x^3-5=0 | | 3*a-b=90 | | x+5*(3x+10)+10=2 | | -12a+10a=-22 | | 21-2x*3=5 | | 5(3y-13)-4y=-21 | | -6m-10m=-16 | | -24=5b+b | | -25=-10x+5x | | -8n-n=-18 | | 14x-25=12x+25 | | 2n+2+4n=2 | | 6x-1=5x+6 | | -11k+9k=-20 | | -11-2k=1+k | | 4b+10b=28 | | 2(k-3)=6 | | n-13+5n=-25 | | 4u-8=-28 | | x-7-12x=37 | | (14)-(-4)= | | cos(3x-180)=-1 | | 8(b+29)=24 | | g=3f+13 | | -(x-2)+3x=-3(x+4)+15 | | 6=-3+36 | | 41=-5x+6 | | 6+6n=-2-2n | | x=6y+11 | | t^3-3t^2+3t-2=0 |

Equations solver categories